Physico-chemical analysis of low calorie high protein shrikhand prepared using stevia leaf powder - Mehrotra, Rolly; DHEER SINGH; AVINASH TIWARI (Innovare Journal of Food Sciences, 2014)
In the present study the textural properties of shrikhand along with the chemical properties were investigated. Based on the preliminary trial sugar was substituted with different ratios of stevia powder. Shrikhand prepared with Stevia powder showed a significant (Pâ‰¤0.05) increase in the proximate composition of shrikhand. The textural parameters decreased with decrease in the amount of sugar significantly (Pâ‰¤0.05). Keywords: Shrikhand, Stevia powder, Nutritive value, texture